Meningkatkan Kualitas Hidup Masyarakat Melalui Pengembangan Potensi Lokal dan Pemberdayaan Komunitas di Desa Lajuk Kabupaten Pasuruan - Mochamad Rizal Aderama; M. Taufiq; Miftakhul Jannah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Community Service Learning (KKN) is a community service program conducted by students of Universitas PGRI Wiranegara. This service activity was carried out in Lajuk Village, Gondang Wetan District, Pasuruan Regency. This study employed a Community-Based Participatory Research (CBPR) approach to involve the community in every stage of the program. The research results showed that the KKN program has successfully improved access to information, environmental awareness, quality of education, and strengthened social and religious bonds in Lajuk Village. Active community participation in every program activity indicates the success of the participatory approach implemented. Overall, this KKN has proven that students can be effective agents of change in village development. Collaboration between students, the community, and the village government is the key to the success of this program. The implementation of this KKN provides important recommendations for the organization of future KKN, namely the importance of involving the community from the early planning stages, selecting work programs that are relevant to the needs of the community, and ensuring the sustainability of programs after the KKN is completed.